Application Of The Preference Selection Index And Method K-Means Clustering Method In Sales Product ( Case Study Of Ocha Cell Store) - Muhammad Anugrah; Herlina Latipa Sari; Rizka Tri Alinse (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2022)
The ocha cell shop is one of the shops engaged in the sale of mobile phones of various brands of mobile phones, the store has not used a special application in processing the products sold, but still uses manual data processing such as recording in a book. So that there is a accumulation of data that is not known for its benefits. One method that can solve this problem is the psi method and the k-means clustering method, because the psi method and the k-means clustering method are methods for solving multiple decision-making criteria, this method is useful if there is a conflict in determining the relative between attributes, so later on the final result of the calculation is that ranking is carried out by analyzing data on sales of goods that are in demand and not selling and the algorithm is partitional by using the value process repeatedly to get the value of the cluster database, it takes the desired number of initial clusters to produce the final ceteroid point as output. With this method, it helps store management to find out which cellphones are often sold and each time a transaction can later help in overcoming existing problems.